The Effect of Dihydrotestosterone Hormone on the Sulfotransferase 1A1 Enzyme Level in the Scalp Hair Follicle in Patients with Androgenic Alopecia and its Effect on Response to Minoxidil - Raghad NA (Journal of Global Pharma Technology, 2018)
Objective:  to evaluate the association between the dihydrotestosterone hormone level and the level of sulfotransferase 1A1 enzyme inside the scalp hair follicle in patients with androgenic alopecia. Method: The study was conducted with the participation of 67 androgenic alopecia patients (37 females and 30 males). The level of serum dihydrotestosterone hormone was estimated using enzyme linked immunosorbent assay. The sulfotransferase enzyme 1A1 was extracted from the plugged scalp hair follicle by sonication and estimated using enzyme linked immunosorbent assay. Results: In this study, it was found that there is a significant association between the level of serum dihydrotestosterone hormone and the level of sulfotransferase 1A1 enzyme inside the scalp hair follicle in patients of androgenic alopecia ( p-value< 0.001), which means that whenever the level of serum dihydrotestosterone hormone increases, the concentration of the sulfotransferase 1A1 enzyme inside the scalp hair follicle decreases, and probably it will affect the response of a patient toward the minoxidil. Conclusion:  reducing the level of serum dihydrotestosterone hormone, could increase the level of sulfotransferase 1A1 enzyme inside the scalp hair follicle and that concept can lead to modulate the treatment regimen of androgenic alopecia.